Influences of the Kuroshio on Interisland Remote Connectivity of Corals Across the Nansei Archipelago in the East China Sea. Issue 12 (25th December 2018) - Uchiyama, Yusuke; Odani, Sachika; Kashima, Motohiko; Kamidaira, Yuki; Mitarai, Satoshi
Abstract: For the preservation and protection of coral habitats along the Nansei Archipelago in the East China Sea, a submesoscale eddy‐resolving synoptic ocean model was developed based on the Regional Oceanic Modeling System coupled with a 3‐D Lagrangian particle tracking model. Millions of neutrally buoyant particles representing coral spawn and larvae were released from 19 major islands and one lagoon every spring from 2012 to 2015. The model results were compared to satellite data, in situ observation, and surface drifters to confirm reasonable agreement. The connectivity matrix across the archipelago was quantified using Lagrangian probability density functions of the modeled particle displacement. Most particles remained near the release areas, while some traveled long distances by the northeastward drifting Kuroshio, leading to notable interisland coral transport across the archipelago that promotes interisland connectivity . A possible mechanism was examined by analyzing the transition from coastal to pelagic transport of the particles released from the Yaeyama Islands, the southernmost area of the archipelago. The Kuroshio trapped the particles released from the northern coast of the islands with considerable temporal variability in the entrainment rate. By contrast, particles released from the southern coast are markedly affected by the eastward current around the release sites, which significantly reduces their entrainment in the Kuroshio and, thus, long‐distance transport. Some entrained particles were expelled abruptly from the Kuroshio, trapped by the southwestward drifting Kuroshio Counter Current developed between the Kuroshio and the archipelago, and subsequently transported eastward to the islands. Plain Language Summary: For the preservation and protection of coral habitats along the Nansei Archipelago in the East China Sea, we conducted 3‐D tracking of particles mimicking coral spawn and larvae released from shallow seas around the islands across the Nansei Archipelago, based on a numerical 3‐D ocean circulation model, Regional Oceanic Modeling System. Although the released corals were mostly transported short distances and settled down near the release sites, a moderate amount was entrained in the northeastward drifting Kuroshio Current developed in ~150 km west of the islands. The entrained particles could be conveyed northeastward for ~1, 000 km, leading to interisland population connections. However, the entrainment rate largely depended on locations of the releases and variability in local oceanic currents upon the releases. Furthermore, some entrained particles were expelled abruptly from the Kuroshio, trapped by the southwestward drifting Kuroshio Counter Current developed between the Kuroshio and the archipelago, and subsequently transported eastward to the islands. These findings can be directly utilized in policy‐making for the effective design management of marine protected areas. Key Points: Dispersal of coral spawn and larvae is investigated using double‐nested circulation modeling coupled with a Lagrangian particle tracking model Corals mostly remain near the release areas, while a nontrivial portion is transported ~1, 000 km over the archipelago due to the Kuroshio Corals are partly separated from the Kuroshio, entrained in the Kuroshio Counter Current, and transported eastward to Okinawa Island